Johanne Luise Heiberg og Mutter Pätges - Christensen, Merete Næsbye (Rambam. Tidsskrift for jødisk kultur og forskning, 2012)
Johanne Luise Heiberg and Mother Pätges In November 2012, the actress Johanne Luise Heiberg would have turned 200 years. She was the daughter of a Jewish mother and a Catholic father, and the seventh of eight children. Johanne Luise and her siblings were not raised with Jewish tradition, and they were all baptised as well as confirmed. Her mother, while not engaged in the Jewish community, did not convert to Christianity, and she lies buried in the Jewish cemetery in Møllegade. Johanne Luise’s life was full of contrasts. She lived part of her childhood at Nørrebro, and the family moved several times during her childhood. But after marrying to wealth, she raised socially. Her mother, Henriette Pätges, had several taverns, one of them in Ulkegade, and Johanne Luise could easily have ended up as a waitress or a show girl. Instead, she succeeded in becoming a famous artist and marrying the famous councillor and theatre manager Johan Ludvig Heiberg. Her success was probably due to a combination of beauty, great talent and the help of good people along the way. The article is illustrated with a series of drawings from 1822 portraying the cheerful and lively environment of the tavern of Mutter Pätges in Ulkegade. It is unknown who made these drawings, but they are now the property of Københavns Museum (Museum of Copenhagen).